Interplay between surface chemistry and performance of rutile-type catalysts for halogen production. Issue 5 (5th February 2016) - Moser, Maximilian; Paunović, Vladimir; Guo, Zhen; Szentmiklósi, László; Hevia, Miguel G.; Higham, Michael; López, Núria; Teschner, Detre; Pérez-Ramírez, Javier
Abstract : DFT, TAP, and operando PGAA studies demonstrate that the complex and dynamic surface chemistry of hydrogen halide oxidation on rutile-type catalysts determines the activity and stability patterns for halogen production. Abstract : Catalytic HBr oxidation is an integral step in the bromine-mediated functionalisation of alkanes to valuable chemicals. This study establishes the relationships between the mechanism of HBr oxidation over rutile-type oxides (RuO2, IrO2, TiO2 ) and their apparent catalytic performance. Comparison with the well-studied HCl oxidation revealed distinct differences in surface chemistry between HBr and HCl oxidation that impact the stability and activity of the catalysts. The kinetic fingerprints of both oxidation reactions over the three rutile-type oxides investigated are compared using temporal analysis of products, which substantiates the energy profiles derived from density functional theory. The quantitative determination of the halogen uptake under operando conditions using prompt gamma activation analysis demonstrates that RuO2 suffers from extensive subsurface bromination upon contact with hydrogen bromide, particularly at low temperature and low O2 : HBr ratios, which negatively affects the stability of the catalyst. TiO2 exhibits intrinsically low halogen coverage (30–50%) under all the conditions investigated, due to its unique defect-driven mechanism that renders it active and stable for Br2 production. On the contrary, for HCl oxidation TiO2 is inactive, and the chlorination of the highly active RuO2 is limited to the surface. Differences in the extent of surface halogenation of the materials were also confirmed by high-resolution transmission electron microscopy and explained by the DFT calculations. These insights into the molecular-level processes taking place under working conditions pave the way for the design of the next generation catalysts for bromine production.